SANITASI KLINIK HEWAN JOGJA - , NIMAS HAPSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sanitation is an attempt to prevent diease by keeping the environmental health, including sanitation management, waste and trash handling, or qualified building construction , in order that the patients and the workers feel safe and comfort. The good sanitation in a clinic will increase the animal and human welfare, but the bad sanitation will obstruct the treatment and recovery of disease. The aim of the study is search whether or not the sanitation in Klinik Hewan Jogja is in accordance with the standard as the animal treatment centre. The data will be collected from interview with some veterinarian, animal clinic workers, and animal clinic owners in Yogyakarta